Recent Developments on Summability Theory and Its Applications - Et, Mikail; Mursaleen, Mohammad; Mohiuddine, Syed Abdul; Isik, Mahmut; Connor, Jeff; Basar, Feyzi (Hindawi Ltd, 2015)
[Abstract Not Available]